Implementasi Kebijakan Penyelenggaraan Pendidikan Profesi Guru (PPG) untuk Sertifikasi Guru PAUD - Ragil, Yoga Aditia; Rahmawati, Yuli; Supena, Asep (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2025)
In-service Teacher Professional Education (PPG) (Daljab) is an educational program designed to produce professional teachers. The program aims to provide prospective teachers with the competencies, skills and knowledge necessary for them to teach effectively in schools. However, in reality, the implementation of PPG still has many obstacles faced by the Educational Institutions for Educational Personnel (LPTK) and PPG participants. The approach used is descriptive qualitative with the number of informants is 12 people with details of 1 from the LPTK, 6 lecturers and 5 from PPG participants. To obtain the data needed in the research, data collection techniques were used in the form of; literature study, interviews, and documentation. The analysis used in this research is by coding, presenting data, and verifying data. The results showed that the implementation process of PPG policy for PAUD teacher certification was not optimal, especially in the aspect of learning theory with minimal interaction, as well as administrative monitoring. Collaborative strategies are needed between LPTK and participants through strengthening infrastructure, and a more interactive learning approach to support the professional competence of PAUD teachers.